Estrutura populacional de ucides cordatus (linnaeus, 1763) em um manguezal hipersalino no semiárido do nordeste brasileiro - Azevêdo, David Vinícius Dantas (2017)
The estuarine ecosystems are of great importance both from the ecological and socioeconomic points of view. Its predominant macrofauna consists of the brachyurus, with emphasis on the Ucides cordatus species. The objective of this work was to characterize the population structure of U. cordatus, in a mangrove area of the Apodi Mossoró River estuary, Rio Grande do Norte. The collections were carried out monthly, from January to December of 2016, in a lunar period of syzygy. The collection technique was by braiding. A total of 633 individuals were collected, of which 585 were males (92.42%), 45 were non-ovigerous females (NOF) (6.79%) and 5 ovigerous females (OF) (0.79%). Male size ranged between 19.30 and 76.66 mm of LC (mean: 59.67 mm; SD: ± 0.27), FNO between 35.4 and 67.60 mm (mean: 51.49 mm; SD: ± 0.99), and FO between 42.7 and 59.8 mm (mean: 48.50 mm, SD: ± 3.0). The sexual ratio (M: F) was 12: 1 did not appear to be equivalent to the expected ratio (1: 1) by the chi-square test. Between the rainy and dry periods there was no significant difference between the males (p = 0.057) and the Mann-Whitney test (p = 0.057). However, when compared to LC of females, there was a significant difference (p = 0.02). The specimens of the species were 2.76 mm (LC), 2.10 mm (CC) and 1.84 mm (HC) larger, and 14.72 g heavier in the dry period when compared to the rainy season. When compared to the Total Weight relation with the body measurements (width, length and height of the carapace) between the periods did not show significance (p> 0.05) by ANCOVA. The growth of the species showed a positive allometry (b> 1) for both periods. The Condition Factor was higher in the rainy season than in the dry period, did not present significance when comparing the periods, through the student t method. The low catchability of many young animals (LC <30 mm) and adults (LC> 70 mm) in the region allows us to infer that this size class has a preference for areas farther from the mouth that allows better environmental conditions, less interspecific competition and little tidal variation